2006
DOI: 10.1179/174328406x102390
|View full text |Cite
|
Sign up to set email alerts
|

Tensile properties of partially austenitised and austempered ductile irons with dual matrix structures

Abstract: In the present study, an unalloyed ductile iron containing Fe-3 . 50C-2 . 63Si-0 . 318Mn-0 . 047Mg (wt-%) were intercritically austenitised (partially austenitised) in two phase region azc at various temperatures of 795, 805, 815 and 830uC for 20 min and then quenched into salt bath held at austempering temperature of 365uC for various times to obtain different ausferrite volume fractions (AFVFs). Results showed that dual matrix structure containing proeutectoid ferrite, new ferrite (also called epitaxial ferr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
0
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(72 citation statements)
references
References 33 publications
3
63
0
6
Order By: Relevance
“…The matrix of a dual phase ADI is composed by ausferrite (as in regular ADI microstructure) and free or allotriomorphic ferrite, in an attempt to combine the high tensile strength and toughness of the ausferrite with the high ductility of ferrite. [15][16][17][18][19][20][21][22][23][24] Different methodologies have been applied to obtain dual phase microstructures. [15][16][17][18][19][20] The simplest method seems to be that described by Basso et al 21,22) and Kilicli et al, 23,24) which consists of an incomplete austenization stage at temperatures within the intercritical interval, where austenite (γ) ferrite (α) and graphite (Gr) coexist (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The matrix of a dual phase ADI is composed by ausferrite (as in regular ADI microstructure) and free or allotriomorphic ferrite, in an attempt to combine the high tensile strength and toughness of the ausferrite with the high ductility of ferrite. [15][16][17][18][19][20][21][22][23][24] Different methodologies have been applied to obtain dual phase microstructures. [15][16][17][18][19][20] The simplest method seems to be that described by Basso et al 21,22) and Kilicli et al, 23,24) which consists of an incomplete austenization stage at temperatures within the intercritical interval, where austenite (γ) ferrite (α) and graphite (Gr) coexist (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The results have revealed that a strong relationship exists between tensile strength and elongation until failure in the case of some Dual Phase ADI microstructures. [4][5][6][7][8] Along these lines, fracture toughness tests have yielded interesting values when compared to those of fully ferritic or fully ausferritic matrices. 4) In view of the fact that many mechanical components used in the industry need tolerate cyclic loads at elevated stresses; another property to be analyzed is fatigue resistance.…”
Section: -3)mentioning
confidence: 99%
“…8, in which the tensile strength-deformation until failure ratio is shown for DI with different microstructures, considering our results as well as those reported by other authors. [4][5][6][7][8][9] …”
Section: Comparative Analysis Among Different Matricesmentioning
confidence: 99%
See 1 more Smart Citation
“…This improvement is explained by the novelty of this DI microstructure, which is composed of different amounts of free (or allotriomorphic) ferrite and ausferrite (ADI regular structure). [1][2][3][4][5][6][7][8][9][10][11] Special thermal cycles have been developed by different researchers in order to obtain Dual Phase ADI. One of them has been advanced and used by Kilicli et al 7,8) and Basso et al [4][5][6] It consists in subjecting fully ferritic DI parts to an incomplete austenitization stage, at different temperatures within the intercritical interval of the Fe-C-Si diagram (see Fig.…”
Section: Introduccionmentioning
confidence: 99%